Modelagem e simulação da cristalização do cloreto de sódio em misturas com água e monoetileno glicol - Souza, João Paulo (2019)
The production of natural gas, on offshore platforms, should avoid the occurrence of hydrates, which are crystalline solids that can block the gas flow ducts. The use of monoethylene glycol (MEG) has efficacy already known in the operational environment in relation to the prevention of hydrates. The MEG is injected into the submerged pipeline and acts as a hydrate inhibitor, as it reduces the freezing point of the fluid produced by the gas reservoir (water + salts + hydrocarbons). This fluid arrives at the platform mixed with the injected MEG, but this must be regenerated/recovered to reuse it. This is possible through an MEG regeneration plant installed on the platform itself. However, it is at this stage that technical difficulties may occur due to the presence of MEG. The water produced by the reservoir is saline and, therefore, the presence of salts can cause incrustations in the MEG regeneration unit, since this substance reduces the solubility of the present salts. The Sodium chloride (NaCl) is the salt with the highest concentration in this system. If the NaCl concentration is above solubility, unwanted precipitation of its crystals may occur. This crystallization and eventual precipitation can cause problems such as incrustations, which are very harmful in some equipment that make up the regeneration plant. This can be accomplished through the use of a computer simulator that can, from the operational conditions of the plant and laboratory data, calculate the concentrations of the species in a timely manner and, if necessary, the amount of salt precipitated during the MEG regeneration process. This work aimed to create a simulator that can perform mass balance calculations to determine the salt concentration and, based on the knowledge of solubility, quantify the occurrence of salt precipitates, only providing the variables temperature, salt concentration in the food, mass fraction of MEG on a salt-free basis and mass flow. The simulator has a graphical interface that allows the user to provide the necessary operational data and, based on that, calculate the salt concentrations in the ternary mixture. The simulator was created using the Python programming language. Due to the existence of a kinetics for the deposition of salt, other solids and impurities, the simulator calculates only the amount of crystallized salt present in the process currents, since precipitation depends on other fluid dynamic factors that are not part of the scope of this study.